Implikasi Pentingnya Pelaksanaan Disiplin Gereja - A Andre; S Susanto (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2020)
In the development of the church today, the problem that arises is the confusion of people who sin, the church seems to ignore the implementation of church discipline. This neglect is wrong attitude, because it does not carry out church discipline that means the church allows a person to fall into sin the reason of fear for making the person offended even though this kind of attitude makes the person's spiritual growth die. Death spiritual growth will become the root of the problem in the church and have an adverse effect on other congregations, therefore church leaders must be brave in making decisions. The method used in this paper is a qualitative method with a descriptive approach. The results of this study indicate that church discipline is very important in correcting mistakes so that the congregation can live righteously according to God's Word. The church needs to be brave in taking decisions in carrying out church discipline, and must not neglect the implementation of church discipline, because church discipline is God's command according to the truth of God's Word.